IMPROVEMENT OF DEPOSIT OPERATIONS IN COMMERCIAL BANKS - P.Sh, Usmanov (Antis Publisher, 2024)
The article presents the nature, economic content, importance of deposit operations of commercial banks, ways of organizing deposit operations, as well as conclusions and suggestions for its improvement